Financial Performance Analysis and Review of Profitability Ratios at The BUMDes Cahaya Makmur - Annisa Almaqfira; irma Irma Alimuddin; Andi Mattulada Amir (Universitas Cenderawasih, 2023)
The purpose of this study was to determine the financial performance of BUMDes Cahaya Makmur in terms of profitability ratios consisting of Gross Profit Margin (GPM), Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE). This type of research is a type of descriptive research using a quantitative approach. The data was obtained from the financial statements of BUMDes Cahaya Makmur in Bakubakulu Village, Palolo District, Sigi Regency for the 2018-2021 period by carrying out data collection techniques through field research, observation, interviews and documentation in the form of photos in BUMDes Cahaya Makmur. The results of data analysis on the profitability ratios of the Cahaya Makmur BUMDes on the Gross Profit Margin ratio in 2018 (95.09% > 24.90%), in 2019 (225.13% > 24.90%), in 2020 (27.75% > 24.90%), and in 2021 (51.91% > 24.90%) with results above the standard until it is said to be quite good even though it has decreased. On the Net Profit Margin ratio of the four years 2018 (95.09% > 3.92%), 2019 (225.13% > 3.92%) and 2020 (27.75% > 3.92%) until 2021 (51.91% > 3.92%) got results that are far above the average value so that it is said to be very good. In the Return On Assets ratio in 2018 (1.07%), in 2019 (1.08%), in 2020 (0.22%) and in 2021 (0.54%) these values are far below the industry standard values Return On Assets (5.98%) so that it has not been used properly, this is the same as the Return On Equity value of the four years, namely 2018 (1.08%), 2019 (1.23%), 2020 (0 .5%) and in 2021 (2.06%) where this value is far below the industry standard Return On Equity (8.32%) which means the results from each year have not been used properly.